Logos that last: how to create iconic visual branding - Peters, Allan (Beverly, MA: Rockport, 2023)
Author Allan Peters is an award-winning graphic designer whose expertise in logos and rebranding has been tapped by major media outlets, including The New York Times and CNN. In this landmark guide for designers and brand strategists of any level, Peters distills his knowledge and experience from over two decades of designing for top brands such as Google, Amazon, Disney, Target, and Nike, as well as personal passion projects.
Keywords: Business; Marketing